Use of permanent hair dyes and cancer among registered nurses. - Hennekens, C; Speizer, F; Rosner, B; Bain, C; Belanger, C; Peto, R (1979)
A survey of 120 557 married, female, registered U.S. nurses, aged 30 to 55 years, carried out in 1976, showed that 38 459 (31·9%) had at some time used hair dyes, and 3548 (2·9%) had had cancer. For all cancers combined, the risk ratio (R.R.) for the development of cancer among women who had used hair dyes at any time, compared with those who had never used them, was 1·10 (P=0·02). When cancers were subdivided by anatomical site into 16 main groups, only those of the cervix uteri (R.R.=1·44, P<0·001) and those of the vagina and vulva (R.R.=2·58, P=0·02) showed statistically significant associations with use of permanent hair dyes. Both these associations were reduced but remained significant after standardisation for cigarette smoking, and neither showed increases in risk of cancer with increasing years since first use of hair dyes. Women who had used permanent dyes for 21 years or more before the onset of cancer had a significant increase in risk for all sites combined (R.R.=1·38, P=0·02), compared with "never users". This increase was primarily due to an excess number of observed to expected cases of breast cancer (24 versus 16·3). However, among those who had first used dye 16 to 20 years before diagnosis of breast cancer, there was an almost equal deficit in numbers of cancers at this site (16 observed versus 25·1 expected). The present evidence does not indicate that any material risk of cancer is likely to have occurred during the initial 20 years following first use of permanent hair dyes. © 1979.